2017
DOI: 10.1155/2017/8736428
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Bioactivity of NeoMTA Plus™ versus MTA Angelus® Root Repair Materials

Abstract: Objectives. To analyse the chemistry and bioactivity of NeoMTA Plus in comparison with the conventional root repair materials. Method and Materials. Unhydrated and hydrated (initial and final sets) materials were analysed by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). For bioactivity study, small holes of dentin discs were filled with either materials, immersed in PBS for 15 days, and analysed with FTIR and scanning electron microscope with energy dispersive X-ray (SEM/EDX). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…The results of FT-IR analysis for TheraCal presented similar bands for alite (Ca 3 SiO 5 ), and apatite (HA-C 10 (PO 4 ) 6 (OH) 2 ) [31], CO 3 2− , SiO 4 4− [32], CSH [33], and calcium carbonate [34], which is similar to literature data, and, after the setting reaction, bands for CSH could be identified. By immersion in SBF, it was observed that characteristic bands of the phosphate groups increased, due to mineralization of the hardened material surface.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of FT-IR analysis for TheraCal presented similar bands for alite (Ca 3 SiO 5 ), and apatite (HA-C 10 (PO 4 ) 6 (OH) 2 ) [31], CO 3 2− , SiO 4 4− [32], CSH [33], and calcium carbonate [34], which is similar to literature data, and, after the setting reaction, bands for CSH could be identified. By immersion in SBF, it was observed that characteristic bands of the phosphate groups increased, due to mineralization of the hardened material surface.…”
Section: Discussionsupporting
confidence: 82%
“…FT-IR analysis performed on the anhydrous BIO MTA+ powder showed bands for CO 3 2− and alite, which is similar to those obtained by Abu Zeid al. [34] and Gandolfi et al [32]. By hydration at 37 °C, R.H. = 100%, calcium silicates were converted into calcium silicates hydrates, with their presence being demonstrated by scanning electron microscopy images through the form of needle-like/foils [35] and FT-IR spectra [32].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the BC paste, if material immersed in NaOCl, the spectra showed dipped OH and CO bands at 2,361 and 2,331 cm −1 respectively (Su et al, 2010). While material immersed in CHX, spectra showed the development of triple NH bands at 1,650–1,550 cm −1 and CN band at 1,249 and 1,061 cm −1 (Lohar et al, 2016; Zounon, Koriko, Kodom, Tchegueni, & Tchangbedji, 2019) and evidence of doublet phosphate bands related to apatite formation at 603 and 580 cm −1 (Abu Zeid et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Mineral/matrix FTIR and carbonate/phosphate FTIR ratios were calculated (Turunen et al, 2011). Deconvolution of infrared spectra was performed at 700–500 cm −1 to identify doublet v 4 phosphate bands (around 600 and 560 cm −1 ), then the crystallinity index (CI) was calculated (Abu Zeid et al, 2017; Lebon et al, 2010). All the parameters were compared among groups using One‐Way analysis of variance (ANOVA) and post hoc test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation